Numerical analysis of meniscus dynamics in monolayer-wick dropwise condensation. (2nd September 2019) - Modak, S.; Kaviany, M.; Hoenig, S.; Bonner, R.
Abstract: The effect of hydrophobic monolayer sintered-particle wick on the growth and departure of droplets in dropwise condensation over a vertical surface is analyzed numerically using the minimum meniscus surface energy principle and the direct simulation of the meniscus and heat transfer through the partially liquid-filled pores. The condensate fills the pores, increases the capillary pressure, and joins with the menisci from adjacent pores, leading to a droplet formation. The droplet growth is supported by liquid supply from the adjacent pores until the critical droplet departure volume is reached. The heat transfer rate is controlled by the average meniscus thickness, and the droplet surface coverage. Based on these and the plain–surface limit (for very small and very large particle diameter d p ), a threshold band of d p is predicted below which the dropwise condensation rate is slightly enhanced compared to the plain, hydrophobic surface. The analysis explains the existing experimental results (and new augmented experimental results) and the challenges in further enhancing the dropwise condensation with surface microstructures.